2017
DOI: 10.3390/medicines4020029
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Antioxidant Activity of Volatile Constituents from Different Parts of Aframomum danielli (Hook) K. Schum

Abstract: Background: Aframomum danielli is used in ethno-medicine for the treatment of several ailments and as a traditional food spice. Methods: The hydro-distilled leaf, stem, seed, rhizome and pod volatile oils of A. danielli were subjected to gas chromatography-mass spectrometry (GC-MS) analysis. Free radical scavenging capacity of the volatile oils was determined using 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) assays. Results: Thirty-nine (39) volatile compounds were identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The results of the chemical composition of essential oils from A. daniellii seeds were in agreement with those of the early reports. Indeed, Essien et al (2017) reported a high content of 1,8-cineole (53.4%), α-terpineol (12.2%) and β-pinene (9.1%) in the essential oil from A. danielli seeds whereas the main compounds identified from the essential oils of this plant collected in Sao Tome were 1,8-cineole (25.5-34.4%), β-pinene (14.1-15.2%) and αterpineol (9.9-12.1%) (Martins et al, 2001). Moreover, Adegoke et al (1998) recorded 1,8-cineole (59.8%), βpinene (13.2%) and α-terpineol (9.3%) in high proportions in the same essential oil from Nigeria, while 1,8-cineole (48.9%) was the main compound of A. danielli seeds collected in Cameroon (Menut et al, 1991).…”
Section: Differences In the Extraction Yields Were Noted Betweenmentioning
confidence: 99%
“…The results of the chemical composition of essential oils from A. daniellii seeds were in agreement with those of the early reports. Indeed, Essien et al (2017) reported a high content of 1,8-cineole (53.4%), α-terpineol (12.2%) and β-pinene (9.1%) in the essential oil from A. danielli seeds whereas the main compounds identified from the essential oils of this plant collected in Sao Tome were 1,8-cineole (25.5-34.4%), β-pinene (14.1-15.2%) and αterpineol (9.9-12.1%) (Martins et al, 2001). Moreover, Adegoke et al (1998) recorded 1,8-cineole (59.8%), βpinene (13.2%) and α-terpineol (9.3%) in high proportions in the same essential oil from Nigeria, while 1,8-cineole (48.9%) was the main compound of A. danielli seeds collected in Cameroon (Menut et al, 1991).…”
Section: Differences In the Extraction Yields Were Noted Betweenmentioning
confidence: 99%
“…Accordingly, the stem, rhizome and pod oils possessed β-pinene, α-phellandrene and γ-terpinene as the major compounds. The oil of leaves was found to be rich in β-pinene, caryophyllene oxide and β-caryophyllene while the seed oil was made of 1,8-cineole, α-terpineol, β-pinene (Essien et al, 2017).…”
Section: A Review On Chemical Constituents Of Essential Oils Ofmentioning
confidence: 99%
“…Furthermore, the seed of A. danielli , which is related to A. corrorima , contained primarily 1, 8-cineole and β-pinene predominated in the leaf, stem, rhizome, and pod oils. In the DPPH assay, the seed oil showed the greatest antioxidant effect [ 20 ]. Currently, the oil most frequently used for frying is palm oil, which is the second-largest source of oil in the world, behind soybean oil (FEDIOL, 2012).…”
Section: Introductionmentioning
confidence: 99%